Asynchronous and synchronous remote teaching and academic outcomes during COVID-19. Issue 3 (3rd July 2022) - Stuart, Jaimee; O'Donnell, Alexander W.; Scott, Riley; O'Donnell, Karlee; Lund, Rochelle; Barber, Bonnie
Abstract: The COVID-19 pandemic has prompted widespread transitions to remote teaching and learning in the higher education sector, bringing challenges for both educators and students. This study investigated links between student engagement with distinct types of remote teaching (asynchronous and synchronous) and academic outcomes (grade point average and academic satisfaction) during the nationwide COVID-19 lockdown in Australia. Connectedness to the university was tested as a moderator of these associations. Results found that students with high levels of university connectedness that engaged more with synchronous teaching had higher grade point averages and academic satisfaction. Conversely, greater engagement with asynchronous teaching was associated with increased satisfaction with academic performance for those low in university connectedness. These findings suggest that both synchronous and asynchronous modes of remote teaching are important for students' academic outcomes and that university connectedness plays a critical role in promoting positive academic experiences and achievement in the context of remote teaching.